2021
DOI: 10.3390/chemistry3030066
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Micro Fibrillated Cellulose (MFC) in Poly(lactic acid) (PLA) from Lab-Scale to Semi-Industrial Processing Using Biobased Plasticizers as Dispersing Aids

Abstract: In the present study, two commercial typologies of microfibrillated cellulose (MFC) (Exilva and Celish) with 2% wt % were firstly melt-compounded at the laboratory scale into polylactic acid (PLA) by a microcompounder. To reach an MFC proper dispersion and avoid the well-known aglomeration problems, the use of two kinds of biobased plasticisers (poly(ethylene glycol) (PEG) and lactic acid oligomer (OLA)) were investigated. The plasticizers had the dual effect of dispersing the MFC, and at the same time, they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This MFR decrement is also reflected in the injection pressure increment during the injection molding process ( Table 2 ). The marked viscosity decrement observed during the lab-scale step is limited, thanks to the coupling of the low extruder residence time and the presence of the venting system connected to a vacuum pump that guarantees the humidity stripping during the melt extrusion, avoiding or limiting any eventual PLA degradation [ 49 , 50 ]. The mechanical results are noteworthy.…”
Section: Resultsmentioning
confidence: 99%
“…This MFR decrement is also reflected in the injection pressure increment during the injection molding process ( Table 2 ). The marked viscosity decrement observed during the lab-scale step is limited, thanks to the coupling of the low extruder residence time and the presence of the venting system connected to a vacuum pump that guarantees the humidity stripping during the melt extrusion, avoiding or limiting any eventual PLA degradation [ 49 , 50 ]. The mechanical results are noteworthy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many researchers found similar results: Molinari, Giovanna et al showed that 9% microcrimped cellulose increases the crystallinity of PLA because it interacts with the amorphous phase of PLA and prevents glassy crystallization. 40 This effect has also been found in the literature, and it can be correlated to the partially amorphous cellulose that modifies the crystallinity of PLA, increasing the disorder of the molecular chain. 42 The OWF has a nucleating effect that can result in an increase in the crystallinity of the composite.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 58%
“…In the literature, the glass transition temperature of PLA is generally around 60°C. 40
Figure 6.DSC thermograms of the films PLA/OWF.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the application of coatings on plastic substrates, this is becoming increasingly necessary with the development of items with novel bio-based and biodegradable plastics based for example on poly (lactic acid) PLA, poly (butylene succinate) PBS, poly(butylene succinate-adipate) PBSA, as they do not show adequate barrier properties and are not able to withstand the rigours of the market [14][15][16][17]. In fact, since they do not present barrier properties comparable to traditional plastics [18], they need a protective layer.…”
Section: Introductionmentioning
confidence: 99%